No reluctant citizens : teaching civics in K-12 classrooms - Clabough, Jeremiah; Lintner, Timothy (Emerald Publishing Limited : Information Age Publishing, Inc., 2018)
"American democracy is in a critical epoch. The rancor among our political parties has been elevated in the aftermath of the contentious 2016 presidential election. There are also many issues dividing Americans: Confederate monuments, NFL players kneeling during the national anthem, healthcare, and claims of fake news to name a few. No Reluctant Citizens: Teaching Civics in K-12 Classrooms is designed to help social studies teachers grapple with these issues. Each chapter focuses on a central issue connected to teaching civic education and provides activities to teach that topic in meaningful ways. Some topics explored include civic literacy, human rights, service learning, and controversial issues. The activities in the chapters give students experience working through issues that they will face as future citizens"-- Provided by publisher.
Keywords: Civics -- Study and teaching -- United States.; Education -- Teaching -- Subjects -- Social Science.; Teaching of a specific subject.; Educational: Social sciences, social studies.; elektronické knihy; electronic books